THE PSYCHOLOGICAL ASPECT OF THE SYNDROME OF EARLY CHILDHOOD AUTISM - Tsarkova, Olga; Prokofieva, Olesia; Anosova, Daria (PSYCHOLOGICAL JOURNAL, 2019)
The article touches the actual issue of significant increase of this pathology in Ukraine and in the world, as well as the need to integrate children with the ECA into the educational environment at the early age. Current research suggests that there is an increasing number of children suffering from a severe developmental disorder - autistic syndrome. Therefore, in recent decades, scientific studies in defectology pay a lot of attention to such anomaly of mental development as early childhood autism. This problem is becoming more and more interested by psychiatrists (especially children ones), psychologists, and educators. Autism is a problem not only for children, but also for their families and society at all. This disorder is often called "hidden" because autistic problems often remain unrevealed. Moreover, at educational institutions, children with autistic tendencies need skilled psychological and pedagogical help, which consists in creating the emotional and psychological comfort environment, raising a sense of confidence and security, and introducing gradually and carefully new skills and behavioural patterns. Diagnosis of early childhood autism is based on the observation method. Recently, more and more attention has been paid to studying and correcting various mental disorders of children. Quite a lot of literature appeared, including recommendations as for mental retardation, impaired learning and upbringing, behavioural and communicative deviations. But still, many more questions remain not fully understood. For example, the problem of early childhood autism (ECA), when communicative disorders prevail in a child’s behaviour and have major influence on his/her anomalous development, while at other mental disorders, communicative problems are secondary or insignificantly small in comparison with the primary disorders: mental retardation, neurotic disorders, speech and hearing defects, and so on. Correction of early childhood autism is a rather difficult task. The syndrome of early childhood autism is associated with special violations of children’s mental development, which baffles their relatives. This problem is very poorly studied and many questions remain open still, which complicates the processes of education, upbringing and correction of such children. Many questions arise in families with such children. At the same time, parents, as a rule, emphasize that they do not consider their children mentally retarded.